Preparation method of negative pole piece of lithium ion battery
By insulating the negative electrode sheet of the lithium battery in a high-temperature furnace, the CMC is decomposed at high temperature to form a conductive structure, which solves the problem of increased resistance caused by CMC adsorption and significantly improves the performance of the battery.
Patent Information
- Application Number
- CN202411712021.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
During the preparation of the negative electrode sheet of the existing lithium battery, CMC is adsorbed on the surface of the negative electrode active material, resulting in an increase in resistance and affecting the overall performance of the battery.
By insulating the negative electrode sheet in a high-temperature furnace, the CMC is decomposed at high temperature to form a conductive structure and chain-like coating of the negative electrode active material is achieved, thereby reducing the resistance.
It effectively reduces the resistivity of the negative electrode sheet, promotes the transmission of electrons and ions, reduces the internal resistance of the battery, and improves the overall performance of the battery.
Smart Images

Figure CN119542360A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a negative electrode sheet of a lithium ion battery. Background Art
[0002] At present, in the lithium battery industry, the conventional formula route for negative electrode sheets is CMC (sodium carboxymethyl cellulose) + SBR (styrene-butadiene rubber) system. As a stabilizer and suspending dispersant, CMC has an auxiliary bonding effect on SBR and can make SBR more evenly dispersed. Its role is mainly reflected in the early stirring step. After the electrode sheet is coated and rolled, CMC is adsorbed on the surface of the active material, which to a certain extent increases the resistance of the negative electrode sheet, thereby affecting the conductive properties of the negative electrode sheet, which is not conducive to the transmission of electrons and ions, and thus reduces the overall performance of the battery.
[0003] Therefore, finding a technical solution that can solve the above technical problems has become an important topic studied by technical personnel in this field. Summary of the invention
[0004] The embodiment of the present invention discloses a method for preparing a negative electrode sheet of a lithium-ion battery, which is used to solve the technical problem that in the existing negative electrode sheet preparation process, CMC is adsorbed on the surface of the negative electrode active material, resulting in an increase in the resistance of the negative electrode sheet, thereby affecting the overall performance of the battery.
[0005] The present invention provides a method for preparing a negative electrode sheet of a lithium ion battery, comprising the following steps:
[0006] The negative electrode active material, the binder, the conductive agent and the dispersing thickener are uniformly stirred in a preset ratio to obtain a negative electrode slurry, wherein the dispersing thickener comprises CMC; the binder comprises SBR;
[0007] The negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and slitting;
[0008] The negative electrode plate is placed in a high temperature furnace and kept warm at a set temperature for a preset time, so that the CMC is decomposed and carbonized at high temperature to form a conductive structure, wherein the set temperature of the high temperature furnace is higher than the temperature at which CMC begins to decompose, and lower than the temperature at which SBR begins to decompose.
[0009] Optionally, the decomposition temperature of the SBR is higher than the decomposition temperature of the CMC by more than 30°C.
[0010] Optionally, the step of placing the negative electrode plate in a high temperature furnace and keeping it warm at a set temperature for a preset time specifically includes:
[0011] The negative electrode coil is fixed on the coil rack and reinforced by a flange ring, and then placed in a high-temperature furnace for heating, wherein the set temperature is 250-350°C and the insulation time is 2-6h.
[0012] Optionally, the set temperature is preferably 275-325°C, and the insulation time is preferably 4-6h.
[0013] Optionally, before the step of keeping the negative electrode coil warm at 250-350° C. for 2-6 hours in the high temperature furnace, the step further includes:
[0014] First, the temperature of the high temperature furnace is set to 80-100° C. and kept at this temperature for 2-4 hours to dehydrate the negative electrode coil.
[0015] Optionally, during the process of heating the negative electrode coil, the high temperature furnace maintains a vacuum state or continuously introduces a protective gas into the high temperature furnace;
[0016] The protective gas is nitrogen or argon.
[0017] Optionally, the negative electrode active material includes one or more of graphite and silicon carbon;
[0018] The conductive agent includes one or more of carbon black, carbon nanotubes, and graphene.
[0019] Optionally, the solid content of the negative electrode slurry is 40%-60%, and the mass percentage of each component is as follows:
[0020] Negative electrode active material: 95.5%-97.5%;
[0021] Conductive agent: 0.1-1.5%;
[0022] CMC: 0.1~1.5%;
[0023] SBR: 1%-2.5%.
[0024] Optionally, the compaction density of the negative electrode layer is 1-3 g / cm 3 The surface density of the negative electrode layer is 20-200 g / m 2 .
[0025] A lithium battery provided by the present invention comprises a positive electrode plate, a separator and a negative electrode plate prepared by the above-mentioned method for preparing a negative electrode plate of a lithium ion battery.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the preparation method of this embodiment, after the negative electrode sheet is formed, it is placed in a high-temperature furnace and kept warm at a set temperature for a preset time. The CMC in the negative electrode sheet is decomposed and carbonized at high temperature to form a conductive structure, and the chain coating of the negative electrode active material is achieved, which greatly reduces the resistivity of the negative electrode sheet. This effectively promotes the transmission of electrons and ions in the electrochemical process, thereby reducing the internal resistance of the battery and improving the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A schematic diagram of a process for preparing a negative electrode sheet of a lithium-ion battery disclosed in the present invention;
[0030] Figure 2 It is a structural schematic diagram of a high-temperature furnace involved in a method for preparing a negative electrode sheet of a lithium-ion battery disclosed in the present invention;
[0031] Figure 3 A schematic diagram of a method for preparing a negative electrode sheet for a lithium-ion battery, in which CMC is decomposed and carbonized at high temperature to form a conductive structure and a chain coating is applied to the negative electrode active material;
[0032] Figure 4 It is a thermogravimetric curve diagram of CMC and SBR in a method for preparing a negative electrode sheet of a lithium-ion battery;
[0033] Illustration: reinforcing rib 1; inner cavity 2; side air duct 3; negative pole coil 4; pole coil rack 5. DETAILED DESCRIPTION
[0034] The invention discloses a method for preparing a negative electrode sheet of a lithium ion battery, which is used to solve the technical problem that in the existing negative electrode sheet preparation process, CMC is adsorbed on the surface of the negative electrode active material, resulting in an increase in the resistance of the negative electrode sheet, thereby affecting the overall performance of the battery.
[0035] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] See also Figures 1 to 4The present invention provides a method for preparing a negative electrode sheet of a lithium-ion battery, comprising the following steps:
[0037] The negative electrode active material, the binder, the conductive agent and the dispersing thickener are uniformly stirred in a preset ratio to obtain a negative electrode slurry, wherein the dispersing thickener includes CMC; the binder includes SBR (it should be noted that CMC is sodium carboxymethyl cellulose, SBR is styrene-butadiene rubber, and the following content is described in terms of CMC and SBR);
[0038] The negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and slitting;
[0039] The negative electrode plate is placed in a high temperature furnace and kept warm at a set temperature for a preset time, so that the CMC is decomposed and carbonized at high temperature to form a conductive structure, wherein the set temperature of the high temperature furnace is higher than the temperature at which CMC begins to decompose, and lower than the temperature at which SBR begins to decompose.
[0040] In the preparation method of the present invention, under the premise of maintaining the physical and chemical properties of SBR to ensure the bonding force, the negative electrode sheet is placed in a high-temperature furnace and kept warm at a set temperature for a preset time. The CMC in the negative electrode sheet is decomposed and carbonized at high temperature to form a conductive structure, and the chain coating of the negative electrode active material is achieved, which greatly reduces the resistivity of the negative electrode sheet. This effectively promotes the transmission of electrons and ions in the electrochemical process, thereby reducing the internal resistance of the battery and improving the performance of the battery.
[0041] In addition, since there is no need to change the negative electrode formula, the invention greatly reduces the risk of abnormal processing of the negative electrode sheet due to formula adjustment. Usually, it is only necessary to adjust the heat treatment temperature and time within the appropriate window to further improve the conductive performance of the negative electrode sheet while ensuring its mechanical properties.
[0042] Specifically, the negative electrode active material in the present invention includes one or more of graphite and silicon carbon; the conductive agent in the present invention includes one or more of carbon black, carbon nanotubes, and graphene; and the negative electrode current collector in the present invention is copper foil.
[0043] It should be noted that the present invention does not limit the specific types of negative electrode active materials, conductive agents and negative electrode current collectors, and designers can select appropriate negative electrode active materials, conductive agents and negative electrode current collectors according to actual conditions.
[0044] Furthermore, the solid content of the negative electrode slurry in the present invention is 40%-60%, and the mass percentage of each component is as follows:
[0045] Negative electrode active material: 95.5%-97.5%;
[0046] Conductive agent: 0.1-1.5%;
[0047] CMC: 0.1~1.5%;
[0048] SBR: 1%-2.5%.
[0049] In addition, in order to ensure the mechanical properties of the negative electrode sheet, the compaction density of the negative electrode layer is 1-3g / cm 3 , surface density is 20-200g / m 2 .
[0050] Furthermore, in the preparation method of this embodiment, the step of placing the negative electrode plate in a high-temperature furnace and keeping it warm at a set temperature for a preset time specifically includes:
[0051] The negative electrode coil is fixed on the coil rack and reinforced by a flange ring, and then placed in a high-temperature furnace for heating, wherein the set temperature is 250-350°C, wherein the set temperature is preferably 275-325°C, and the insulation time is 2-6h, wherein the insulation time is preferably 4-6h.
[0052] It should be noted that reinforcing the negative electrode coil by means of a flange ring can effectively prevent the negative electrode sheet from expanding and thickening.
[0053] In addition, during the high temperature furnace heating process, the decomposition temperature of the SBR is higher than the decomposition temperature of the CMC by more than 30°C.
[0054] It should be noted that the preparation method of the present invention requires that the selected SBR has a decomposition temperature that is 30°C higher than that of CMC, thereby providing a certain window for the carbonization temperature of CMC and reducing the negative impact of uncontrollable factors. The high-temperature furnace is set to a temperature lower than the temperature at which SBR begins to decompose, so as to ensure the bonding performance during the heat treatment process and ensure that the peeling force between the negative electrode layer and the negative electrode current collector meets the strength requirements.
[0055] The thermogravimetric curves of CMC and SBR selected in the subsequent examples are as follows: Figure 4 ,from Figure 4 It can be learned that CMC begins to decompose at about 250°C, and SBR begins to decompose at about 330°C.
[0056] It should be further explained that, ideally, the carbonized CMC ratio should reach 100%, which can reduce the resistivity of the negative electrode plate with maximum efficiency, and the CMC carbonization temperature range is T CMC分解温度 ~T SBR分解温度The time required depends on the actual situation. Generally speaking, CMC needs a longer carbonization time under the condition of lower temperature in this range, while the carbonization time of CMC can be effectively shortened under the condition of higher temperature in this range. When the temperature is lower than the above range, it will make it difficult for CMC to decompose and carbonize, while when it is higher than the upper limit of the above range, it will affect the stable existence state of SBR.
[0057] Furthermore, before the step of keeping the negative electrode coil warm in a high temperature furnace at 250-350° C. for 2-6 hours, the method further includes:
[0058] First, the temperature of the high temperature furnace is set to 80-100° C. and kept at this temperature for 2-4 hours to dehydrate the negative electrode coil.
[0059] It should be noted that the above-mentioned dehydration treatment can effectively prevent the subsequent rapid escape of water molecules at high temperature, which may lead to expansion of the negative electrode sheet, reduced strength, and increased internal resistance, which is beneficial to reducing the resistivity of the negative electrode sheet.
[0060] Furthermore, during the heating process of the negative electrode coil in the high temperature furnace, the high temperature furnace is kept in a vacuum state or a protective gas is continuously introduced;
[0061] The protective gas is nitrogen or argon.
[0062] It should be noted that the above design can prevent high-temperature oxidation of the negative electrode plate.
[0063] The present invention also provides a lithium battery, wherein the lithium battery comprises a positive electrode plate, a separator and a negative electrode plate prepared by the above-mentioned method for preparing a negative electrode plate of a lithium ion battery.
[0064] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0065] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0066] Example 1
[0067] Embodiment 1:
[0068] 1) Select the formula of graphite: SP (carbon black): CMC: SBR = 96.5: 1: 1: 1.5, and obtain the negative electrode slurry by stirring. After coating, rolling and slitting, place the negative electrode sheet in a high-temperature furnace filled with nitrogen for dehydration treatment, the temperature is set to 90°C, the time is set to 3h, and then high-temperature heat treatment is performed, the temperature is set to 300°C, and the time is set to 4h.
[0069] 2) Select a formula of LCO (lithium cobalt oxide): SP (carbon black): PVP (polyvinyl pyrrolidone): PVDF (polyvinylidene fluoride) = 98:0.3:0.5:1.2, obtain a positive electrode slurry by stirring, and then apply, roll and divide into strips.
[0070] 3) Assemble the negative electrode sheet in step 1, the positive electrode sheet in step 2, the commercial separator and the electrolyte into a lithium-ion battery.
[0071] Embodiment 2:
[0072] Based on Example 1, the high temperature heat treatment temperature was set to 250°C.
[0073] Embodiment 3:
[0074] Based on Example 1, the high temperature heat treatment temperature was set to 275°C.
[0075] Embodiment 4:
[0076] Based on Example 1, the high temperature heat treatment temperature was set to 325°C.
[0077] Embodiment 5:
[0078] Based on Example 1, the high temperature heat treatment temperature was set to 350°C.
[0079] Embodiment 6:
[0080] Based on Example 1, the high temperature heat treatment time is set to 2 hours.
[0081] Embodiment 7:
[0082] Based on Example 1, the high temperature heat treatment time is set to 6 hours.
[0083] Comparative Example 1:
[0084] Based on Example 1, the high-temperature heat treatment process for the negative electrode plate is eliminated.
[0085] Experimental results:
[0086] A series of experiments were conducted on the lithium-ion batteries made in the various embodiments and comparative examples to obtain the data shown in Table 1.
[0087]
[0088]
[0089] Table 1
[0090] It can be seen from Table 1 above that when the negative electrode sheet was not heat-treated in Comparative Example 1, the resistivity of the negative electrode sheet and the internal resistance of the lithium-ion battery were relatively large, while in Examples 1-7, due to the heat treatment at a certain time and temperature, the resistivity of the negative electrode sheet and the internal resistance of the lithium-ion battery decreased to varying degrees. The reason is that CMC is carbonized at high temperature to form a conductive structure and realize the chain coating of the negative electrode main material. This experiment effectively verifies the improvement of battery performance by CMC high-temperature carbonization technology. At the same time, it is also noted that the battery cycle retention rate of Example 5 is significantly lower than that of other groups. The reason is that the decomposition of SBR destroys the effective bonding between the graphite particles in the electrode sheet, resulting in poor stability of the negative electrode layer during the cycle and intensified battery polarization.
[0091] The influence of heat treatment temperature on performance can be analyzed from Examples 1, 2, 3, 4, 5 and Comparative Example 1. Figure 4 The thermogravimetric curve analysis shown in the figure shows that when the temperature is 250°C, the carbonization degree of CMC is low, and the resistivity of the negative electrode sheet decreases slightly; when the temperature is 275°C, the carbonization degree of CMC increases, and the resistivity of the negative electrode sheet decreases significantly; when the temperature is 300°C and 325°C, the resistivity of the negative electrode sheet decreases further, which indicates that the carbonization degree of CMC is still deepening, but combined with the changes in the resistivity of the negative electrode sheet in Example 1 and Example 4, it can be roughly judged that CMC has been basically carbonized at 300°C; and when the temperature rises to 350°C, the resistivity of the negative electrode sheet decreases more, but it is not prominent compared to 325°C, and the cycle performance of the assembled battery is significantly deteriorated, so it is necessary to strictly control the heat treatment temperature.
[0092] The effect of heat treatment time on performance can be analyzed from Examples 1, 6, 7 and Comparative Example 1. When the temperature is 300°C and the time is 2h, the resistivity of the negative electrode sheet is significantly reduced compared with Comparative Example 1; when the heat treatment time is extended to 4h, the decline is significantly increased; and when the time is set to 6h, the resistivity of the negative electrode sheet decreases, but it is not obvious compared with Example 1. In order to control production costs, it is recommended to select 4h as the heat treatment time. In addition, the battery cycle performance of these groups of negative electrode sheet assemblies is comparable, proving that 300°C is a more suitable heat treatment temperature.
[0093] The peel strength of the negative electrode sheet after heat treatment was also tested. The experimental results showed that when the temperature set for CMC carbonization did not exceed the thermal decomposition temperature of SBR, the peel strength of the negative electrode sheet increased to varying degrees. It is speculated that SBR can slowly flow in the sheet in a molten state to form a more uniform dispersion state, which strengthens the bonding between the negative electrode layer and the copper foil. When the temperature reaches 350°C, the peel strength of the negative electrode sheet decreases significantly. This is because the temperature exceeds the decomposition temperature of SBR, causing SBR to carbonize and decompose. Although the resistivity of the negative electrode sheet has further decreased, the overall performance of the battery is reduced due to the insufficient bonding provided by SBR.
[0094] The above is a detailed introduction to the preparation method of the negative electrode plate of a lithium-ion battery provided by the present invention. For a person skilled in the art, according to the idea of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation of the present invention.
Claims
1. A method for preparing a negative electrode sheet of a lithium ion battery, characterized in that: The following steps are involved: The negative electrode active material, the binder, the conductive agent and the dispersing thickener are uniformly stirred in a preset ratio to obtain a negative electrode slurry, wherein the dispersing thickener comprises CMC; the binder comprises SBR; The negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and slitting; The negative electrode plate is placed in a high temperature furnace and kept warm at a set temperature for a preset time, so that the CMC is decomposed and carbonized at high temperature to form a conductive structure, wherein the set temperature of the high temperature furnace is higher than the temperature at which CMC begins to decompose, and lower than the temperature at which SBR begins to decompose.
2. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 1, characterized in that: The decomposition temperature of the SBR is higher than the decomposition temperature of the CMC by more than 30°C.
3. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 2, characterized in that: The step of placing the negative electrode plate in a high temperature furnace and keeping it warm at a set temperature for a preset time specifically includes: The negative electrode coil is fixed on the coil rack and reinforced by a flange ring, and then placed in a high-temperature furnace for heating, wherein the set temperature is 250-350°C and the insulation time is 2-6h.
4. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 3, characterized in that: The set temperature is preferably 275-325° C., and the insulation time is preferably 4-6 hours.
5. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 3, characterized in that: Before the step of keeping the negative electrode coil warm at 250-350° C. for 2-6 hours in the high temperature furnace, the following steps are further included: First, the temperature of the high temperature furnace is set to 80-100° C. and kept at this temperature for 2-4 hours to dehydrate the negative electrode coil.
6. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 4, characterized in that: During the heating process of the negative electrode coil by the high temperature furnace, the high temperature furnace is kept in a vacuum state or a protective gas is continuously introduced; The protective gas is nitrogen or argon.
7. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 1, characterized in that: The negative electrode active material includes one or more of graphite and silicon carbon; The conductive agent includes one or more of carbon black, carbon nanotubes, and graphene.
8. The method for preparing a negative electrode sheet for a lithium ion battery according to claim 1, characterized in that: The solid content of the negative electrode slurry is 40%-60%, and the mass percentage of each component is as follows: Negative electrode active material: 95.5%-97.5%; Conductive agent: 0.1-1.5%; CMC: 0.1~1.5%; SBR: 1%-2.5%.
9. The method for preparing a negative electrode sheet for a lithium-ion battery according to claim 1, characterized in that: The compaction density of the negative electrode layer is 1-3 g / cm 3 The surface density of the negative electrode layer is 20-200 g / m 2 .
10. A lithium battery, characterized in that: The invention comprises a positive electrode sheet, a separator and a negative electrode sheet prepared by the method for preparing a negative electrode sheet for a lithium-ion battery as claimed in any one of claims 1 to 9.
Citation Information
Cited By
Conductive network construction process method of solid-state battery
CN120356906A